Accessibility Mainstreaming and Beyond – Senior Citizens as Secondary Users of Audio Subtitles in Cinemas - JANKOWSKA, ANNA (International Journal of Language, Translation and Intercultural Communication, 2019)
Audiovisual accessibility is traditionally seen as a means of providing access for people with sensory impairments, be it sight or hearing loss (Orero, 2004). Recently, a much broader perspective opened as some also see it as a way of providing linguistic accessibility (Díaz Cintas, 2005; Orero & Matamala, 2007) or even as services that cater for the specific needs of people who "cannot, or cannot properly, access the audiovisual content in its original form" (Greco, 2016: 23). This article fits squarely into this trend as it reports on a survey-based study set out to find out preferences regarding linguistic accessibility in the cinema among unimpaired senior citizens in Poland. On the whole, 40 people aged 60 or more took part in the study. Results show that senior citizens are more likely to choose voice-over and dubbing over subtitling. This could be because the majority of participants declared that they experience discomfort or difficulties when reading subtitles. As a result, they are willing to use a mobile app that would enable them to listen to audio subtitles in the cinemas.